Odontogenic myxoma: a clinicopathological study over 15 years and immunohistochemical analysis - Juengsomjit, Rachai; Arayasantiparb, Raweewan; Ghazali, Ahmad Badruddin; Kosanwat, Theerachai (Elselvier, 2024)
Objective: and rationale: Odontogenic myxoma is an uncommon odontogenic tumor with locally aggressive behavior. The clinicopathological studies of odontogenic myxoma in Asian countries are very limited and only few studies have investigated the immunohistochemical profiles of the tumor. This study aims to investigate the clinicopathological and immunohistochemical features of odontogenic myxoma at the Faculty of Dentistry, Mahidol University over a 15-year period. Methods: Archives of our institute were reviewed. Cases diagnosed as odontogenic myxoma were retrieved. Demographic, clinical, radiographic, and histopathological features of these cases were analyzed. In addition, immunohistochemical markers including vimentin, Ki-67, Bcl-2, and CD117 were performed. The correlation between immunohistochemical profiles and clinicopathological characteristics was evaluated. Results: Sixteen cases of odontogenic myxoma were discovered. Fourteen cases were central type while two cases were peripheral type. The mean age of patients was 34.6 years with male-tof emale ratio of 1:2.2. Mandible (68.8 %) was more affected than the maxilla (31.2 %). Bony expansion or jaw swelling (43.8 %) was the most common clinical feature. Most cases (71.4 %) presented with multilocular radiolucency. Histopathologically, tumors show stellate and pindle shaped cells in a myxoid stroma with varying amounts of collagen fiber. All cases were positive for vimentin and Bcl-2. Half of the cases showed positive for Ki-67. Mast cells were presented in most cases (75.0 %). A significant correlation was found between the immunoexpression level of Bcl-2 and border of lesion in radiograph (p = 0.024). Conclusions: This study contributes to better understanding of the characteristics of odontogenic myxoma. Clinicians and pathologists should be aware of odontogenic myxoma, as its clinical and histopathological features may overlap with other tumors. The expression of Bcl-2 and presence of mast cell in this tumor may relate to its growth and aggressiveness. Despite its benign nature, odontogenic myxoma exhibits high recurrence, especially in lesion managed conservatively.